CODE-SWITCHING IN AN INDONESIAN-FRENCH MIXED MARRIED FAMILY - Sang Ayu Putu Ari Purniawati; Luh Putu Artini; Ni Luh Putu Sri Adnyani (Lingua Scientia, 2019)
Code-switching is a common phenomenon in bilingual/multilingual community. The study investigates the code-switching from grammatical view in a mixed married of Indonesian-French wife-husband. The participants of the study were the mixed married and their three children. The data were obtained through video recording, observation, note-taking, and anecdotal recording of daily conversations between or among the family members in house domain that were analyzed qualitatively. It is found out that they commit code-switching either Inter or Intra-sentential one in communicating to each other.